Law and lawlessness in Early Judaism and Early Christianity - Lautenschlaeger Colloquium on Law and Lawlessness in Early Judaism and Christianity 2015 Oxford; Lincicum, David 1979-; Sheridan, Ruth 1980-; Stang, Charles M. 1974-; Mohr Siebeck GmbH & Co. KG (Tübingen Mohr Siebeck, 2019)
Cover -- Titel -- Preface -- Contents -- Introduction -- Lutz Doering: Law and Lawlessness in Texts from Qumran -- Grant Macaskill: Law and Lawlessness in the Enoch Literature -- Joshua D. Garroway: Paul: Within Judaism, Without Law -- Paula Fredriksen: Origen and Augustine on Paul and the Law -- David M. Moffitt: Weak and Useless? Purity, the Mosaic Law, and Perfection in Hebrews -- David Lincicum: Against the Law: The Epistle of Barnabas and Torah Polemic in Early Christianity -- Paul F. Bradshaw: The Ancient Church Orders: Early ecclesiastical law? -- Steven D. Fraade: Rabbis on Gentile Lawlessness. Three Midrashic Moments -- Michal Bar-Asher Siegal: Law Corpora Compared: Early Collections of Monastic Rules and Rabbinic Literature -- Christopher Rowland: "By an immediate revelation … by the voice of his own spirit to my soul": A perspective from Reception History on the New Testament and Antinomianism -- Michael Peppard: Law and Liberty: Circumcision Discourse from Galatia to Germany -- List of Contributors -- Index of Ancient Sources -- Index of Modern Authors -- Subject Index.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Konferenzschrift -- 2015 -- Oxford